Dieting practices and body image perception among Lebanese university students - Rizk, Sandra (2011)
Dieting is becoming a popular phenomenon among university students to achieve or maintain a healthy weight. The purpose of this study is to obtain a preliminary understanding of what dieting practices university students use in order to achieve their desirable body weight and to determine the magnitude of body dissatisfaction in relation to weight status among a sample of students (n=252) from the Lebanese American University in Beirut, Lebanon. Students filled out a self-reported questionnaire that included questions on their dieting and physical activity practices in addition to the body shape questionnaire (BSQ). Weight and height were measured to calculate body mass index. Percentage body fat was measured using Tanita scale body fat analyzer 300A. The outcome of this study showed that smoking and unhealthy dieting practices were not common among students (only 26% reported smoking, 8% reported taking laxatives and 4% taking diet pills). Half of the students reported practicing regular physical activity. Multivitamin intake was also not popular among students. BSQ scores indicate that the majority of students were not worried about their body image perception (64% reported not being worried, 19% were slightly worried, 12% were moderately worried and 5% were extremely worried). A gender difference was observed in the BSQ scores, as 89% of the "extremely worried" students were females. Collectively, results indicate that unhealthy dieting practices are uncommon among students. However, developing health promotion awareness' programs to promote good self image within the concept of a realistic healthy weight will be beneficial, especially among females.